Pengaruh Persepsi Manfaat, Persepsi Kemudahan Terhadap Minat Menggunakan Aplikasi Fintech dengan Kepercayaan Sebagai Variabel Intervening pada Generasi Z Kota Medan - Nurhayati; Ade Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of perceived ease and perceived usefulness on interest in using fintech applications through trust. This research adopts a quantitative associative methodology, where every individual from generation Z who lives in the city of Medan becomes the population and sample. To determine the sample size, the Lemeshow method was used, which determined a minimum of 384 respondents to participate to fill out a questionnaire with a Likert scale. The collected data was then analyzed using the PLS-SEM approach with the SmartPLS tool. Research findings reveal that perceived convenience has a significant influence on interest in using fintech applications. Perception of ease has a significant effect on confidence in using fintech applications. Perceived benefits have a significant effect on interest in using fintech applications. Perceived benefits have a significant effect on confidence in using fintech applications. Trust has a significant effect on interest in using fintech applications. Perception of ease has a significant effect on interest in using fintech applications through trust. Perceived benefits have a significant influence on interest in using fintech applications through trust in generation Z in the city of Medan.